Development of new COD sensor - Luo, Zhengyang. (2009)
The Chemical Oxygen Demand (COD) is the amount of oxygen consumed to completely chemically oxidize organic water components to inorganic end products. Water quality is determined by factors such as physical state, chemical concentrations and biological organisms. COD which reflects the total pollution load in the water samples is a very important parameter in both water treatment and assessment.